2012
DOI: 10.1016/j.bbr.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in methamphetamine-induced dopaminergic toxicity mediated by protein kinase Cδ

Abstract: This study examined the role of protein kinase C (PKC) isozymes in methamphetamine (MA)-induced dopaminergic toxicity. Multiple-dose administration of MA did not significantly alter PKCα, PKCβI, PKCβII, or PKCζ expression in the striatum, but did significantly increase PKCδ expression. Gö6976 (a co-inhibitor of PKCα and -β), hispidin (PKCβ inhibitor), and PKCζ pseudosubstrate inhibitor (PKCζ inhibitor) did not significantly alter MA-induced behavioral impairments. However, rottlerin (PKCδ inhibitor) significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 94 publications
1
75
0
Order By: Relevance
“…Consistent with these studies, we demonstrated in an in vivo study that administering rottlerin, a PKC␦-specific inhibitor, protected against MPTP-induced loss of tyrosine hydroxylase-positive neurons in the nigrostriatum and the depletion of striatal dopamine and its metabolites, as well as MPTP-induced locomotor deficits (16). In a methamphetamine-intoxicated animal model, PKC␦ deficiency and rottlerin effectively attenuated methamphetamine-induced dopaminergic damage and behavioral deficits, further supporting that PKC␦ could represent a valid pharmacological target for the treatment of dopaminergic neuronal degeneration (17,18). Interestingly, we also showed that PKC␦ negatively modulates dopamine synthesis by inhibiting the rate-limiting enzyme, tyrosine hydroxylase (3).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Consistent with these studies, we demonstrated in an in vivo study that administering rottlerin, a PKC␦-specific inhibitor, protected against MPTP-induced loss of tyrosine hydroxylase-positive neurons in the nigrostriatum and the depletion of striatal dopamine and its metabolites, as well as MPTP-induced locomotor deficits (16). In a methamphetamine-intoxicated animal model, PKC␦ deficiency and rottlerin effectively attenuated methamphetamine-induced dopaminergic damage and behavioral deficits, further supporting that PKC␦ could represent a valid pharmacological target for the treatment of dopaminergic neuronal degeneration (17,18). Interestingly, we also showed that PKC␦ negatively modulates dopamine synthesis by inhibiting the rate-limiting enzyme, tyrosine hydroxylase (3).…”
mentioning
confidence: 62%
“…We then proceeded to analyze the 6-OHDA-induced oxidative toxicity by MTS viability and dopamine reuptake assays. To determine the effects of PKC␦, we applied the PKC␦ inhibitor rottlerin, which has been shown to protect against MPTP and methamphetamine dopaminergic neurotoxicity and alleviate LPS-induced neuroinflammation both in vitro and in vivo (16,18,85). Our preliminary analyses indicate 0.3 M rottlerin for a 24-h treatment would be optimal for differentiated LUHMES cells (data not shown).…”
Section: Functional Studies In Human Dopaminergic Neuronal Cells and mentioning
confidence: 99%
“…Likewise, protein kinase Cδ knock-out animals have reduced lipid peroxidation, protein oxidation, and behavioral deficits in response to methamphetamine. These studies were corroborated using pharmacological interventions, which also indicate increased tyrosine hydroxylase phosphorylation in response to methamphetamine (Shin et al, 2011, 2012). …”
Section: Partmentioning
confidence: 79%
“…We failed to observe MA‐induced TUNEL‐positive cells in the striatum of WT mice 12 hr, 1 day, or 3 days after the final MA administration (i.e., four injections of 8 mg/kg MA, intraperitoneally at 2‐hr intervals or a single injection of MA 20–40 mg/kg), suggesting that the C57BL/6 background is not sensitive to TUNEL staining . Thus, according to the previous reports , we used 10‐wk‐old male Taconic ICR mice. Because apoptotic cell death was detectable at 20 mg/kg MA and reached a significant level at 35 mg/kg in our previous study, a 35 mg/kg dose of MA was chosen for the present study.…”
Section: Resultsmentioning
confidence: 98%